Systematic Review: Development Of English Modules For Physical Therapy In Improving English Language Skills For Physical Therapy Students - Ahmad Nurwanto; Melli Anisa Putri; Muhammad Rizali (CV. ITTC INDONESIA, 2025)
Proficiency in English is an essential skill for physiotherapy students, given the extensive medical literature published in English and the necessity for effective communication with international patients. Therefore, the development of the